Potensi Sumber Energi Terbarukan dari Biomassa yang Berasal dari Sumber Daya Alam di Balikpapan - Febrianti, Nia; Filiana, Firilia; Hasanah, Primadina (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Biomass energy sources have several advantages, such as being used as a renewable energy source so that the energy source from biomass can provide a sustainable energy source. One of the first steps to determine the potential of energy resources that can be developed into renewable energy sources is by collecting data. The data collection carried out in this study focuses more on the biomass found in Balikpapan. The biomass potential in Balikpapan needs to be known by collecting and classifying the biomass data based on products from agriculture and plantations. The data that has been collected from secondary data and from surveys are then mapped to see the greatest biomass potential found in Balikpapan. The largest percentage of crop yields per year is found in North Balikpapan Subdistrict, which is 31% compared to five other sub-districts. The potential of biomass from Balikpapan City's natural resources, which the greatest amount of harvest, is the cassava food plant in North Balikpapan sub-district of 7,259 tons / year. In the type of fruit, snakefruit (salak) has the highest number of yields per year, which is about32,945 tons / year. The potential for waste from food plants, cassava waste originating from tree trunks, is 5,807.2 tons / year, and cassava skin is 1,088.8 tons / year